2012
DOI: 10.4194/1303-2712-v12_4_08
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Age, growth, mortality and reproduction of the chub mackerel (Scomber japonicus Houttuyn, 1782) , t 0 =-2.13 year for all samples. It was observed that spawning period occured between June and August. The length at first maturity was estimated as 18.0 cm for all samples. Total mortality rate (Z), natural mortality rate (M), fishing mortality rate (F) and exploitation rate (E) of the chub mackerel were 0.91 year -1 , 0.34 year -1 , 0.57 year -1 and 0.62 year -1 , respectivelyKeywords: Stock structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Such differences may be due to different habitats, methods used length range, and number of specimens. The growth performance index (Ø) of 2.68 was higher than some previous studies (Aguayo & Steffens,1986;Kiparissis et al, 2000 andCengiz 2012), but lower than others (Tuggac, 1957;Mendo, 1984;Perrotta, 1992, Lorenzo et al, 1995, Perrotta et al, 2005, Gang et al, 2008and Samuel et al, 2016. Differences in habitats were correlated with increasing age at the high growth performance shown in the table, whereas the present index and others with lower values were slightly similar to the same/lower age groups.…”
Section: Discussionmentioning
confidence: 55%
“…Such differences may be due to different habitats, methods used length range, and number of specimens. The growth performance index (Ø) of 2.68 was higher than some previous studies (Aguayo & Steffens,1986;Kiparissis et al, 2000 andCengiz 2012), but lower than others (Tuggac, 1957;Mendo, 1984;Perrotta, 1992, Lorenzo et al, 1995, Perrotta et al, 2005, Gang et al, 2008and Samuel et al, 2016. Differences in habitats were correlated with increasing age at the high growth performance shown in the table, whereas the present index and others with lower values were slightly similar to the same/lower age groups.…”
Section: Discussionmentioning
confidence: 55%
“…Finally, in the Atlantic Iberian waters spawning season has been reported from December to March in waters of southern Portugal waters (ICES 2020), from December to May in western Portuguese waters (Nunes et al 2019) and, lastly, from March to July on the northwestern Spanish coast and the Cantabrian Sea (Villamor et al 2017Navarro et al 2021a). The spawning period of Atlantic chub mackerel in the Mediterranean Sea has been reported from April to August (Rizkalla 1998, Cengiz 2012, Allaya et al 2013. Our results show a clear latitudinal gradient of spawning season onset and duration that matches with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The shelf extends at a water depth of 90-120 m. The length of the bay is about 61 km and the width at the opening to the Aegean Sea is about 36 km (Eronat and Sayin, 2014). Cengiz (2012) reported that the spawning period of the chub mackerel occurred between April and August with a peak in June in the Saros Bay. Therefore, 35 fully mature females S. japonicus were sampled with handline during the spawning season in 2014 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%